(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The main goal of the research is to reveal philosophically the essence and specificity of the legal culture in a life of modern society. In accordance with this goal, the following problems are posed and solved in the study: – to conduct a systematic analysis of the material accumulated in theory and social practice relevant to the topic; – to reveal the essence and specificity of legal culture as a significant spiritual and social phenomenon; – to disclose the substantive basis of the notion of value orientations; – to present the youth’s value orientations, innovations in value orientations, taking place in the conditions of social transformations of Kazakhstan in the modern stage. Theoretical and methodological basis of the research are the works of the classics of the world and domestic philosophy and theory of law. The methodological basis is the program documents of development – independent Kazakhstan on the path of building a legal state and civil society, in which the factor of legal culture occupies a significant and necessary place. The strategic guidelines of the right-cultural transformations are set forth in the works of the President of the Republic of Kazakhstan – N.A. Nazarbayev. The task is to understand two immutable rules. First, no modernization can take place without preserving the national culture. Secondly, in order to move forward, we must abandon those elements of the past that do not allow the nation to develop (Nazarbayev, 2017). An important theoretical basis of the work are the works of modern philosophers, culturologists, jurists, political scientists, sociologists and educators. The initial methodological principles of problem analysis are: the unity of induction and deduction, empirical and theoretical, historical and logical, abstract and concrete, comparative analysis, etc. The scientific and practical importance of the research is determined by the fact that its results can be used in the development of courses in philosophy, political science, sociology and other humanitarian disciplines, they can prove useful in the work of the media, internal policy departments and other state structures in shaping public opinion, when studying the trends in the development of mass consciousness. Key words: youth, value orientations, society of transitional type, law culture, socialization, development.